2020
DOI: 10.1111/pace.14107
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the cardiac conduction system

Abstract: The specialized cardiomyocytes that constitute the conduction system in the human heart, initiate the electric impulse and result in rhythmic and synchronized contraction of the atria and ventricles. Although the atrioventricular (AV) conduction axis was described more than a century ago by Sunao Tawara, the anatomic pathway for propagation of impulse from atria to the ventricles has been a topic of debate for years. Over the past 2 decades, there has been a resurgence of conduction system pacing (CSP) by impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 28 publications
1
66
0
2
Order By: Relevance
“…Moreover, a lesser risk of TR could also be presumed with HBP by the fact that the lead tip and body are potentially above the tricuspid valve and within the right atrium 30–33 . However, recent anatomical studies showed HBP leads often penetrate the central fibrous body into the insulating tissues (representing the transition from the AV node to the bundle of His) on the atrial side of the hinge‐line in just over one‐half of the cases, and in the remainder either at the hinge‐line or on its ventricular aspect 34,35 . In agreement with this observation, we found HBP lead location below the TV in up to 43% of the cases; nevertheless, even though we appreciated a significant improvement in TR within each HBP subgroup of lead position (above and below the TV), we found no significant differences in TR severity between these two subgroups at 6‐months.…”
Section: Discussionmentioning
confidence: 75%
“…Moreover, a lesser risk of TR could also be presumed with HBP by the fact that the lead tip and body are potentially above the tricuspid valve and within the right atrium 30–33 . However, recent anatomical studies showed HBP leads often penetrate the central fibrous body into the insulating tissues (representing the transition from the AV node to the bundle of His) on the atrial side of the hinge‐line in just over one‐half of the cases, and in the remainder either at the hinge‐line or on its ventricular aspect 34,35 . In agreement with this observation, we found HBP lead location below the TV in up to 43% of the cases; nevertheless, even though we appreciated a significant improvement in TR within each HBP subgroup of lead position (above and below the TV), we found no significant differences in TR severity between these two subgroups at 6‐months.…”
Section: Discussionmentioning
confidence: 75%
“…In this study, we analyzed leaflet sectors of the aorticvalvular complex with respect to the need for PPI. Usually, patients requiring PPI had larger right coronary cusp (RCC) or noncoronary coronary cusp (NCC) sector calcification in the region of the leaflets (Dasi et al, 2017;Li and Sun, 2017;Lin et al, 2020;Padala et al, 2021). When a prosthesis was deployed within a severely and asymmetrically calcified leaflet during TAVR, there was a large pressure generated from the calcified leaflets.…”
Section: Feature Extractionmentioning
confidence: 99%
“…The right bundle branch travels toward the moderator band and the anterolateral papillary muscle. Lastly, they both culminate in the sub-endocardium, respectively, in the left and the right ventricles, by connecting with Purkinje fibers that contribute to the transmission of the electrical signal to the endocardial ventricular regions (Padala et al, 2021 ).…”
Section: Anatomy Biology and Physiology Of The Cardiac Conduction Systemmentioning
confidence: 99%
“…In the path toward natural rhythm restoration ( Figure 1 ), several technological advances are deeply contributing to an increased understanding of conductance (patho)physiology (Franco and Icardo, 2001 ; Goodyer et al, 2019 ; van Eif et al, 2020 ; Padala et al, 2021 ), as well as to its more feasible addressing for resolution. Methodologies based on naturally pacing cells, stem cell differentiation, gene engineering, tissue engineering, and/or their combination have been rehearsed so far in vitro and in vivo with varying success rates in restoring adequate cardiac pacing and conduction.…”
Section: Approaches For the Engineering Of Biological Pacemakersmentioning
confidence: 99%